PERAN MEDIASI MOTIVASI KERJA PADA STRES KERJA DAN BEBAN KERJA TERHADAP KINERJA KARYAWAN DI KANTOR PEMANGKUAN HUTAN - Riski Fitria Dewi; Mochamad Nurhadi; Emma Julianti; Tjahjani Prawitowati (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2023)
This study aims to analyze the direct effect of work stress, workload, work motivation on employee performance. Also analyze the indirect effect of work stress, workload on employee performance mediated by work motivation. The sampling technique used purposive sampling with a total of 120 employees of the Forest Management Office in East Java. The analysis technique used in this research is PLS-SEM. The results showed that work stress did not affect employee performance, but work stress had a positive effect on workload. Workload does not affect employee performance, but workload has an influence on work motivation, and work motivation affects employee performance. Work motivation is also able to mediate the relationship between workload and employee performance, and workload and work motivation serially mediate the relationship between work stress and employee performance. Work stress and workload do not directly affect employee performance, but mediated by work motivation there is an influence between work stress and workload on employee performance.